Ticagrelor potentiates adenosine-induced stimulation of neutrophil chemotaxis and phagocytosis - Alsharif, Khalaf F. (Vascul Pharmacol, 2015)
In the PLATO study, ticagrelor was associated with fewer pulmonary infections and subsequent deaths than clopidogrel. Neutrophils are a first-line defence against bacterial lung infection; ticagrelor inhibits cellular uptake of adenosine, a known regulator of neutrophil chemotaxis and phagocytosis. We assessed whether the inhibition of adenosine uptake by ticagrelor influences neutrophil chemotaxis and phagocytosis. Neutrophils and erythrocytes were isolated from healthy volunteers. Concentration-dependent effects of adenosine on IL-8-induced neutrophil chemotaxis were investigated and the involved receptors identified using adenosine receptor antagonists. The modulatory effects of ticagrelor on adenosine-mediated changes in neutrophil chemotaxis and phagocytosis of Streptococcus pneumoniae were determined in the presence of erythrocytes to replicate physiological conditions of cellular adenosine uptake. Low-concentration adenosine (10(− 8) M) significantly increased IL-8-induced neutrophil chemotaxis (% neutrophil chemotaxis: adenosine 28.7% ± 4.4 vs. control 22.6% ± 2.4; p < 0.01) by acting on the high-affinity A(1) receptor. Erythrocytes attenuated the effect of adenosine, although this was preserved by ticagrelor and dipyridamole (another inhibitor of adenosine uptake) but not by control or by cangrelor. Similarly, in the presence of erythrocytes, a low concentration of adenosine (10(− 8) M) significantly increased neutrophil phagocytic index compared to control when ticagrelor was present (37.6 ± 6.6 vs. 28.0 ± 6.6; p = 0.028) but had no effect in the absence of ticagrelor. We therefore conclude that the inhibition of cellular adenosine reuptake by ticagrelor potentiates the effects of a nanomolar concentration of adenosine on neutrophil chemotaxis and phagocytosis. This represents a potential mechanism by which ticagrelor could influence host defence against bacterial lung infection.